Selection and Interpretation of Scientific Evidence in Preparation for Policy Decisions: A Case Study Regarding Introduction of Rotavirus Vaccine Into National Immunization Programs in Sweden, Norway, Finland, and Denmark - Gry St-Martin; Ann Lindstrand; Synne Sandbu; Thea Kølsen Fischer; Thea Kølsen Fischer (Frontiers in Public Health, 2018)
The World Health Organization recommends inclusion of rotavirus vaccines in national immunization programs (NIPs) worldwide. Nordic countries are usually considered comparable in terms of demographics and health-care services and have comparable rotavirus disease burden. Nevertheless, the countries have reached different decisions regarding rotavirus vaccine: Norway and Finland have already introduced rotavirus vaccines into their NIPs and Sweden is currently changing its recommendation and vaccines will now be introduced on a national scale while Denmark has decided against it. This study focuses on the selection and interpretation of medical and epidemiological evidence used during the decision-making processes in Sweden, Norway, Finland, and Denmark. The so-called “severity criteria” is identified as one of the main reasons for the different policy decisions reached across the Nordic countries.